Speed and Energy Efficiency of a Fish Robot Featuring Exponential Patterns of Control - Ivan Tanev (Actuators)
Fish in nature have evolved more efficient swimming capabilities compared to that of propeller-driven autonomous underwater vehicles. Motivated by such knowledge, we discuss a bionic (bio-memetic) autonomous underwater vehicle—a fish robot—that mimics the swimming of rainbow trout (Oncorhynchus mykiss) in nature. The robot consists of three (anterior, posterior, and tail) segments, connected via two (anterior and posterior) actuated hinge joints. We divided the half-period of undulation of the robot into two phases—thrusting and braking. In addition, we hypothesized that an asymmetric duration—a short period of thrusting and a long period of braking—implemented as an exponential (rather than “canonical”, sinusoidal) control would favorably affect the net propulsion of these two phases. The experimental results verified that, compared to sinusoidal undulation, the proposed exponential control results in increased speed of the robot between 1.1 to 4 times in the range of frequencies of undulation between 0.4 Hz and 2 Hz, and improved energy efficiency from 1.1 to 3.6 times in the same frequency range.